Association of VEGF and p53 Polymorphisms and Spiral Artery Remodeling in Recurrent Pregnancy Loss: A Systematic Review and Meta-Analysis - Subi, Tamil Mani; Krishnakumar, Vinodhini; Kataru, Chandreswara Raju; Panigrahi, Inusha; Kannan, Meganathan (Thrombosis and Haemostasis, 2021)
Many studies have reported the association of VEGF-1154G/A, VEGF 936C/T, and p53 Arg72Pro polymorphisms with recurrent pregnancy loss (RPL), but the outcomes are inconsistent. We have used a meta-analysis to associate these polymorphisms with RPL, having the spiral artery remodeling as a major risk factor. The studies were identified from three different reputed databases, namely ScienceDirect, PubMed/Medline, and Scopus. The eligible studies of VEGF-1154G/A, VEGF 936C/T, and p53Arg72Pro polymorphisms associated with the RPL were selected for the analysis. They were segregated into three different ethnic groups as Asians, Caucasians, and mixed population. For the analysis, the overall prevalence, odds ratio, risk ratio, relative risk ratio, and p-values were calculated. A total of 3,241 RPL cases and 3,205 healthy controls from 21 different case–control studies were analyzed. RPL was highly prevalent in the mixed population with VEGF-1154G/A and p53 Arg72Pro polymorphisms (70.04 and 66.46%, respectively) and in the Asian population with VEGF 936C/T polymorphism (53.58%). The homozygous recessive genotypes of VEGF and p53 exhibited significant association between the respective polymorphisms and RPL along with the increased risk of outcome. The current analysis conclusively reports the geographic distribution of the different genetic polymorphisms which shows high association with the progression of RPL. Understanding the spectrum of polymorphisms on different populations with the spiral artery remodeling as a risk factor encloses the importance of the vasculature during the pregnancy.
Keywords: association; p53; VEGF; polymorphisms; RPL